THE EFFECT OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON STOCK RETURNS IN TEXTILE AND GARMENT SUB-SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE (IDX) - Ni Kadek Mawar Sri Widyastuti; I Gde Kajeng Baskara Soewardikoen (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The capital market serves as an essential platform for investors to earn returns through stock investments. Stock returns are a key indicator for evaluating investment performance and are crucial in investors' decision-making processes. Returns reflect the profit or gain from stock investments and act as a benchmark of a company's performance in the capital market. However, the significant fluctuations in stock returns among textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023 indicate instability, potentially undermining investor confidence. This study aims to analyze the effect of profitability (ROA), liquidity (CR), and leverage (DER) on stock returns in textile and garment sub-sector companies on the IDX during the 2020–2023 period. The sample consists of 18 companies selected using a non-probability sampling method. The study adopts a quantitative approach with multiple linear regression analysis. The results reveal that profitability has a positive and significant effect on stock returns, while liquidity and leverage have no significant effect. These findings suggest that a company's ability to generate profits is a key signal considered by investors in evaluating the potential returns of a stock.